Long Non-coding RNA LINC01969 Promotes Ovarian Cancer by Regulating the miR-144-5p/LARP1 Axis as a Competing Endogenous RNA - Chen, Jinxin; Li, Xiaocen; Yang, Lu; Zhang, Jingru (Frontiers in Cell and Developmental Biology, 2021)
Accumulating evidence has shown that long non-coding RNAs (lncRNAs) can be used as biological markers and treatment targets in cancer and play various roles in cancer-related biological processes. However, the lncRNA expression profiles and their roles and action mechanisms in ovarian cancer (OC) are largely unknown. Here, we assessed the lncRNA expression profiles in OC tissues from The Cancer Genome Atlas (TCGA) database, and one upregulated lncRNA, LINC01969, was selected for further study. LINC01969 expression levels in 41 patients were verified using quantitative real-time polymerase chain reaction (qRT-PCR). The in vitro effects of LINC01969 on OC cell migration, invasion, and proliferation were determined by the CCK-8, ethynyl-2-deoxyuridine (EdU), wound healing, and Transwell assays. Epithelial–mesenchymal transition (EMT) was evaluated using qRT-PCR and Western blotting. The molecular mechanisms of LINC01969 in OC were assessed through bioinformatics analysis, RNA-binding protein immunoprecipitation (RIP), dual luciferase reporter gene assays, and a rescue experiment. Finally, in vivo experiments were conducted to evaluate the functions of LINC01969. The results of the current study showed that LINC01969 was dramatically upregulated in OC, and patients with lower LINC01969 expression levels tended to have better overall survival. Further experiments demonstrated that LINC01969 promoted the migration, invasion, and proliferation of OC cells in vitro and sped up tumor growth in vivo. Additionally, LINC01969, which primarily exists in the cytoplasm, boosted LARP1 expression by sponging miR-144-5p and promoted the malignant phenotypes of OC cells. In conclusion, the LINC01969/miR-144-5p/LARP1 axis is a newly identified regulatory signaling pathway involved in OC progression.